2020
DOI: 10.1002/cmdc.202000070
|View full text |Cite
|
Sign up to set email alerts
|

Reduction‐Triggered Doxorubicin Delivery by Self‐Assembled Nanospheres of Lipoylated Caffeine

Abstract: This study reports a new amphiphilic bioconjugate (CAFF‐LA) derived from the lipoylation of a hydroxyethyl derivative of caffeine. In water, CAFF‐LA self‐assembles into nanospheres with an average size of 155 nm, as evidenced from dynamic light scattering and electron microscopy studies. The nanospheres are stable in serum and could be disintegrated upon exposure to the reducing environment of dithiothreitol (DTT; 10 mM) and glutathione (GSH; 10 mM). These nanospheres easily encapsulate the chemotherapy medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…To investigate the antibacterial properties of caffeine copolymers with hydrophilic charged groups, we prepared libraries of random copolymers through free-radical polymerization. Caffeine polymer derivatives are known to be accessible by free radical polymerization through methacrylate functionalization at the 8-position or 7-position of the caffeine heterocycle or by polymerization of lipoylated caffeine . In the current study, we used etofylline, a derivative of caffeine bearing an ethyl alcohol side chain at the 7-position and functionalized with a methacrylate (Caf-MA) by nucleophilic substitution of methacryloyl chloride in a 56% yield (Figures S1 and S2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the antibacterial properties of caffeine copolymers with hydrophilic charged groups, we prepared libraries of random copolymers through free-radical polymerization. Caffeine polymer derivatives are known to be accessible by free radical polymerization through methacrylate functionalization at the 8-position or 7-position of the caffeine heterocycle or by polymerization of lipoylated caffeine . In the current study, we used etofylline, a derivative of caffeine bearing an ethyl alcohol side chain at the 7-position and functionalized with a methacrylate (Caf-MA) by nucleophilic substitution of methacryloyl chloride in a 56% yield (Figures S1 and S2).…”
Section: Resultsmentioning
confidence: 99%
“…Caffeine polymer derivatives are known to be accessible by free radical polymerization through methacrylate functionalization at the 8-position 42 or 7-position 43 of the caffeine heterocycle or by polymerization of lipoylated caffeine. 44 In the current study, we used etofylline, a derivative of caffeine bearing an ethyl alcohol side chain at the 7-position and functionalized with a methacrylate (Caf-MA) by nucleophilic substitution of methacryloyl chloride in a 56% yield (Figures S1 and S2). Free-radical homopolymerization of Caf-MA (30 equiv) was performed using azobis(isobutyronitrile) (AIBN, 1 equiv) in dimethyl sulfoxide (DMSO) under argon at 75 °C.…”
Section: Polymer Preparationmentioning
confidence: 99%
“…Figure G,I shows that the fluorescence intensity of the GSH-treated group was higher than that of the non-GSH-treated group, especially the Res NPs + GSH group (70.74 ± 0.78). This indicated that after the endocytosis of the NPs, the disulfide bond was destroyed under the redox stimulation, and the drug was released in the cell, which led to a higher accumulation of the drug in the cell . Therefore, these targeted NPs showed promising therapeutic effects, especially those drugs lacking therapeutic targets.…”
Section: Results and Discussionmentioning
confidence: 99%
“…This indicated that after the endocytosis of the NPs, the disulfide bond was destroyed under the redox stimulation, and the drug was released in the cell, which led to a higher accumulation of the drug in the cell. 52 Therefore, these targeted NPs showed promising therapeutic effects, especially those drugs lacking therapeutic targets. 3.7.…”
Section: Resultsmentioning
confidence: 99%